Evaluation of mortality and readmissions following hospitalization with heart failure. (2nd October 2016) - Swindle, Jason P.; Chan, Wing W.; Waltman Johnson, Katherine; Becker, Laura; Blauer-Peterson, Cori; Altan, Aylin
Abstract: Objective: To examine the association of patient/clinical characteristics with mortality and readmission following a heart failure (HF)-related hospitalization. Research design and methods: Claims data, linked to laboratory, race/ethnicity, and mortality data, from a large US health plan were utilized to identify individuals with ≥1 inpatient claim with a diagnosis code for HF (1 January 2008–30 September 2012). Study variables were analyzed using descriptive and multivariable approaches to identify patient/clinical characteristics associated with post-discharge outcomes. Main outcome measures: Primary outcomes included post-discharge mortality and readmission. Results: A total of 126, 214 individuals were identified with a HF-related hospitalization; 19.1% with data to calculate chronic kidney disease (CKD) stage. For the overall sample, mortality probability was 4.9% and 13.4% at 1 and 6 months post-discharge, respectively (4.5% and 12.4% for subset with calculated CKD stage), while readmission (all-cause) probability was 14.8% and 39.6% at 1 and 6 months post-discharge, respectively (18.4% and 44.5% for subset with calculated CKD stage). Within the subset with calculated CKD stage, mortality and readmission probabilities differed by CKD stage ( p < 0.001), with decreased renal function corresponding with increased risk of mortality and readmission. After multivariable adjustment, increasing age was associated with increased risk of mortality, while advancing CKD stage, various index hospitalization variables (i.e., pre-admission emergency room visit, intensive care unit during hospitalization), and baseline all-cause hospitalization were associated with both increased risk of mortality and all-cause 1 month readmission. Conclusions: Calculated CKD, various index hospitalization variables, and baseline all-cause hospitalization were associated with increased risk of mortality and all-cause 1 month readmission among patients hospitalized with HF. Risk of post-discharge readmission and mortality increased with worse renal function, suggesting that improved management of this subset may reduce the burden and cost of this disease. Key study limitations include those related to retrospective claims-based studies and that renal function data were available for a subset of study patients.